ANALISIS SINTAKSIS KALIMAT MAJEMUK DALAM TEKS BERITA PADA MEDIA DARING KOMPAS.COM - Nabila Rahma Aulia; Muhammad Ihsan Hayatul Barokah; Erlina Nur Fajriyanti; Asma Izzati; Iis Lisnawati (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This study aims to analyze the syntactic structure of compound sentences in online news texts on Kompas.com media. Using qualitative descriptive methods, this study identifies the structure, types, and functions of compound sentences in the news text entitled